Cooperación al desarrollo y demandas étnicas en los Andes ecuatorianos by Víctor Bretón Zolo de Zaldívar - Ferraro, Emilia (2001)
Review of Cooperación al desarrollo y demandas étnicas en los Andes ecuatorianos